Proposta de apropriação de makerspaces de escolas públicas baseada no protagonismo dos alunos - Marafon, Gustavo (2025)
This research is situated in the field of Education, specifically focusing on Learning Maker Laboratories—spaces that foster creativity and experimentation through the “do-it-yourself” culture. Traditional schools, in terms of their methods and pedagogical approaches, often do not allow students to act as protagonists in their own learning processes. In this context, a metamorphosis of the school is sought—a transformation toward more meaningful education. The Learning Maker Laboratories, recently implemented in schools, offer new ways to approach the teaching and learning paradigm. However, collected data show that these spaces are still not intensively used in the school routine. It is assumed that a process based on greater student participation could have positive effects on this appropriation. Therefore, this study seeks to answer the following research question: what are the contours of a process of appropriation of school-based Maker Laboratories grounded in student protagonism? The objective is to describe how this appropriation occurs through the organization, engagement, and participation of students. To achieve this, a maker group was formed, and an intervention was conducted in a public school in Passo Fundo, RS, Brazil. The methodology is qualitative, using a field diary and a semi-structured interview with the laboratory monitor, focusing on data analysis based on categories related to student protagonism, such as lived experiences, collective provocations, individual achievements, decision-making, and application of theoretical knowledge. The results show that Learning Maker Laboratories can promote student protagonism by fostering autonomy, collaboration, engagement, and responsibility. The investigation revealed that when students see themselves as active participants, the appropriation of the space becomes more meaningful, connecting school and life in a transformative educational perspective.